Avaliação do ciclo de vida da areia em mineradora de pequeno porte, na região de São José do Rio Preto - SP - Souza, Ariane de (2012)
The mining of sand, although of great socio-economic importance to the national scene, has several negative impacts throughout the production chain. Among some of the interference in the natural environment occurs, soil degradation, air pollution and stress in the fauna and flora. This fact has generated great interest in mechanisms that mitigate or prevent adverse effects on the natural environment, such as the Life Cycle Analysis (LCA), which through mass balances and energy gains can provide socio-economic and environmental. The objective of this research was to evaluate the life cycle of the sand extracted from a riverbed mining in the small region of Sao Jose do Rio Preto in the stages of extraction, processing, storage and transport of sand. For this purpose, the procedures were based on ISO standards 14040 and 14044, which require the determination of he purpose and scope, inventory analysis, environmental impact assessment (conducted through the EDIP method (Environmental Development of Industrial Products)) and interpretation. There was a visit to a mining company to collect information on techniques, technologies and inputs used in the production process. In determining the scope, purpose, system boundaries, scales, functional unit and other details were defined. The other steps involved the standardization of units of measurement, classification of environmental changes, normalization and weighting. As a result, it was found that the higher are the atmospheric emissions of carbon dioxide followed by nitrogen oxides and carbon monoxide, whereas potential environmental impacts are most significant global warming and ozone photochemical formation. So, are recommended as the main mitigating actions: activities aimed at optimizing the extraction of sand, implementation of a program for managing the vehicle fleet and dredges and resizing of centrifugal pumps.